Determinants of healthcare workers' willingness to recommend the seasonal influenza vaccine to diabetic patients: A cross-sectional survey in Ningbo, China. Issue 12 (2nd December 2018) - Ye, Lixia; Chen, Jieping; Fang, Ting; Cui, Jun; Li, Hui; Ma, Rui; Sun, Yexiang; Li, Pingping; Dong, Hongjun; Xu, Guozhang
ABSTRACT: Background : Seasonal influenza vaccine uptake among diabetic patients is low in China. Recent studies showed healthcare workers'(HCWs') recommendation is an effective way to promote influenza vaccination. This study aimed to assess HCWs' willingness to recommend influenza vaccine to diabetic patients and identify the predictors of this willingness. Methods : During Dec 2016-Jan 2017, a self-administered questionnaire on perceptions, attitudes and practices related to influenza vaccination for diabetic patients was distributed to 1370 HCWs in 20 hospitals and 20 community health centers in Ningbo. Predictors of HCWs' willingness to recommend influenza vaccine were analyzed by logistic regressions. Results : Of 1340 HCWs who completed the survey, 58.13%(779/1340) participants reported willingness to recommend influenza vaccine to diabetic patients. Factors positively associated with the recommendation willingness included awareness of national influenza vaccination guideline(OR: 6.33; 95%CI: 4.66–8.60) and regional reimbursement policy(OR: 1.62; 95%CI: 1.19–2.20), training on influenza and diabetes (OR: 1.65; 95%CI: 1.21–2.23), influenza vaccination history(OR: 1.35; 95%CI: 1.01–1.79), beliefs in vaccine effects on reducing serious consequences(OR: 1.38; 95%CI: 1.01–1.91), reduction in hospitalization costs(OR: 1.43; 95%CI: 1.05–1.94) caused by influenza, and more than 10 years of practitioner experience(OR: 1.60; 95%CI: 1.04–2.46). Worries about side-effects of influenza vaccine were identified as the barriers of recommendation. Conclusion : The present study demonstrates that knowledge about national guideline and reimbursement policies, training programs, perceptions about effectiveness and safety of influenza vaccine increase HCWs' willingness to recommend the influenza vaccination to diabetic patients. These measures should be taken to ensure HCWs' role in the administration of influenza vaccination among diabetic patients.